A Novel and Efficient Synthetic Route to (±)-Serinolamide A via Aziridine Ring Opening and Amide Coupling - Amardeep Ramprasad Jadhao; Adinath Devidas Badar; Pramod Shahajee Phatak; Kiran Fulchand Shelke; Jyotipal Jaiprakash Khadse; Nikhil Bhikaji Umbarkar; Santosh Babanrao Gaikwad (International Journal of Scientific Research in Chemistry, 2025)
(±)-Serinolamide A, a serinol-derived fatty acid amide, plays an important role in cannabinoid receptor modulation. While existing synthetic approaches rely on direct amidation or enzymatic coupling, we present a new, efficient and modular synthetic route utilizing selective aziridine ring opening followed by amide bond formation with fatty acid chloride. This method offers enhanced regioselectivity, scalability, and adaptability to structural analogs.